Supplement to the knowledge of the Tachinus longicornis-group (Coleoptera: Staphylinidae: Tachyporinae) in China - Chang, Yuan; Li, Li-Zhen; Yin, Zi-Wei (Zootaxa, 2019)
A new species of the Tachinus longicornis-group of the subgenus Tachinoderus Motschulsky, i.e., T.  motuoensis Chang, Li & Yin, sp. nov., is described from Xizang, China. New collecting records are provided for T. (Tachinoderus) bilobus Chang, Li & Yin and T. (Tachinoderus) ohbayashii Li, Zhao & Sakai in Hubei.